PENDATAAN MASYARAKAT KURANG MAMPU SEBAGAI SASARAN DANA BAKSOS DESA SIDOMUKTI KEMBANGBAHU LAMONGAN - Ika Farida Yuliana; Arufatun Naimah (TAAWUN, 2021)
The pandemic period that hit Indonesia in 2020 has a real impact on underprivileged people in the Lamongan area, especially in the village of Sidomukti. The economic impact is felt by all parties so that when the Thematic KKN Universitas BIllfath is carried out one group, namely group 6 carries out Social Service activities. Social service is aimed at underprivileged people who are also affected by the Covid-19 pandemic. Before social service is carried out, the data collection process needs to be carried out to obtain definite data regarding the underprivileged people who are targeted. This data collection is carried out with the hope that the funds distributed will be right on target to the people in need. This data collection method is carried out in collaboration with the village government by looking at the data that is owned by the village government and going directly to the field to ensure the accuracy of the data. The results of the data collection show that there are 30 families classified as underprivileged and deserving of social assistance funds. The data obtained were then submitted to the social service fund distribution team for immediate follow-up.